2012
DOI: 10.1007/s00438-012-0675-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of Aux/IAA gene family in Solanaceae species using tomato as a model

Abstract: Auxin plays key roles in a wide variety of plant activities, including embryo development, leaf formation, phototropism, fruit development and root initiation and development. Auxin/indoleacetic acid (Aux/IAA) genes, encoding short-lived nuclear proteins, are key regulators in the auxin transduction pathway. But how they work is still unknown. In order to conduct a systematic analysis of this gene family in Solanaceae species, a genome-wide search for the homologues of auxin response genes was carried out. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 66 publications
10
52
0
Order By: Relevance
“…Functional analysis and expression profiling of ARF, GH3 and AUX/IAA genes are helpful to reveal the mechanisms how auxin regulates plant growth and development and responses to environmental changes in a spatio-temporal specific manner. Recently, these three gene families have been widely characterized in plants such as 23 AtARFs, 19 GH3s and 29 AUX/IAAs in Arabidopsis (Remington et al 2004;Okushima et al 2005;Staswick et al 2005), 25 OsARFs, 12 OsGH3 s and 31 OsAUX/IAAs in rice (Jain et al 2006;Mukesh et al 2006;Wang et al 2007), 16 CsARFs, 10 CsGH3 s and 27 CsAUXIN/IAAs in cucumber (Wu et al 2014), 35 ZmARFs, 13 ZmGH3 s and 31 ZmAUX/IAAs in maize (Wang et al 2010;Liu et al 2011;Feng et al 2015) and 17 SlARFs, 15 SlGH3s and 26 SlAUX/IAAs in tomato (Kumar et al 2011(Kumar et al , 2012Wu et al 2012). In this study, 22 CitARFs, 11 CitGH3 s and 26 CitAUX/IAAs have been identified in citrus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional analysis and expression profiling of ARF, GH3 and AUX/IAA genes are helpful to reveal the mechanisms how auxin regulates plant growth and development and responses to environmental changes in a spatio-temporal specific manner. Recently, these three gene families have been widely characterized in plants such as 23 AtARFs, 19 GH3s and 29 AUX/IAAs in Arabidopsis (Remington et al 2004;Okushima et al 2005;Staswick et al 2005), 25 OsARFs, 12 OsGH3 s and 31 OsAUX/IAAs in rice (Jain et al 2006;Mukesh et al 2006;Wang et al 2007), 16 CsARFs, 10 CsGH3 s and 27 CsAUXIN/IAAs in cucumber (Wu et al 2014), 35 ZmARFs, 13 ZmGH3 s and 31 ZmAUX/IAAs in maize (Wang et al 2010;Liu et al 2011;Feng et al 2015) and 17 SlARFs, 15 SlGH3s and 26 SlAUX/IAAs in tomato (Kumar et al 2011(Kumar et al , 2012Wu et al 2012). In this study, 22 CitARFs, 11 CitGH3 s and 26 CitAUX/IAAs have been identified in citrus.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their potential importance, GH3, ARF and AUX/ IAA gene families have been widely identified and characterized in great number of plant species, such as populus (Kalluri et al 2007;Yang et al 2014b), Medicaga truncatula (Shen et al 2014), soybean (Ha et al 2013), apple (Yuan et al 2013), Vitis vinifera (Wan et al 2014), Cucumis sativus (Gan et al 2013), rice (Jain et al 2006;Wang et al 2007), maize (Wang et al 2010;Liu et al 2011) and tomato (Kumar et al 2011(Kumar et al , 2012Wu et al 2012). However, no data on these gene families are available in citrus.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure analysis revealed that Bem1p (PB1) domain in C-terminal is the special domain for the protein-protein interaction between Aux/IAA and ARF [14]. Moreover, Aux/IAA proteins contain two nuclear localization signals (NLS), which locate Aux/IAA proteins to the nucleus [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…3 In tomato, genome-wide analysis identifies 26 putative AUX/IAA genes. 4 Suppression of SlIAA3 produced auxin and ethylene-related developmental defects, such as reduced apical dominance and exaggerated hook in etiolated seedlings.…”
mentioning
confidence: 99%